Size at maturity of the Pacific bearded brotula (Ophidiidae: Brotula clarkae): a commercially exploited species in the Pacific of Costa Rica - Herrera Sarrias, Marcela (2016)
The deep-water shrimp fishery is of great commercial importance along the Pacific coast of Latin America. In Costa Rica, shrimp resources have declined considerably over the last decade. Therefore, fisheries have shifted towards teleost species such as the Pacific bearded brotula Brotula clarkae. Little is known about the biology and life history of this species, which is becoming increasingly valuable to artisanal and semiindustrial fishers in Costa Rica. A sample of 348 B. clarkae was obtained along the Pacific coast of Costa Rica between March 2011 and July 2012 to obtain baseline information of this species. The results revealed that the size at sexual maturity of B. clarkae was 71.9 cm TL, considerably higher than previously reported for South American populations. Since the size at maturity may vary between populations in different geographic locations, detailed information of the reproductive biology of widely distributed species such as B. clarkae is critical for developing effective management approaches.